2007
DOI: 10.2170/physiolsci.rp010006
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Pharmacological Characterization of the KATP Channel Involved in the K+-Current Responses to FSH and Adenosine in the Follicular Cells of Xenopus Oocyte

Abstract: Abstract:The follicular cells surrounding Xenopus oocyte under voltage clamp produce K + -current responses to follicle-stimulating hormone (FSH), adenosine (Ade), and intracellularly applied cAMP. We previously reported that these responses are suppressed by the stimulation of P2Y receptor through phosphorylation by PKC presumably of the ATP-sensitive K + (K ATP ) channel. This channel comprises sulfonylurea receptors (SURs) and K + ionophores (Kirs) having differential sensitivities to K + channel openers (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Subunit identification of endogenous K ATP channels in follicular cells remains currently unknown. A recent study suggested that a novel type of Kir6.1/SUR2A combination comprises endogenous K ATP channels (Fujita et al, 2007 For many years, Xenopus oocytes have served as a model system for studying intricate mechanisms of follicle maturation and cell cycle control (Brown, 2004). In vivo, stage VI immature oocytes are physiologically arrested in the first meiotic prophase at the G 2 /M border, and they resume meiosis when gonadotropins stimulate surrounding follicle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Subunit identification of endogenous K ATP channels in follicular cells remains currently unknown. A recent study suggested that a novel type of Kir6.1/SUR2A combination comprises endogenous K ATP channels (Fujita et al, 2007 For many years, Xenopus oocytes have served as a model system for studying intricate mechanisms of follicle maturation and cell cycle control (Brown, 2004). In vivo, stage VI immature oocytes are physiologically arrested in the first meiotic prophase at the G 2 /M border, and they resume meiosis when gonadotropins stimulate surrounding follicle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chromanol 293b, an inhibitor of slow delayed rectifier K ϩ current (IKs) (3, 16) had minimal effect. Tolbutamide and phentolamine, inhibitors of K ATP channels (21), and charybdotoxin, which acts on BK CA and K V channels (48,66), had no effects. Although the published K i of charybdotoxin is 0.5 nM and the concentration we used was 50 nM, 100-fold above the K i , this concentration of charybdotoxin would be insufficient to Fig.…”
Section: In Vitro Perfusion Of Shark Rectal Glandsmentioning
confidence: 94%
“…Typical K ATP channels consist of an inwardrectifier K + ionophore (Kir6.x) and a sulfonylurea receptor (SURx); there are 2 Kir6.x isoforms (Kir6.1 and 6.2), and 3 SUR isoforms (SUR1, SUR2A, and SUR2B). Although 6 combinations of Kir6.x and SURx can be formed, only 4 types of K ATP channel have been reported: those found in pancreas β-cells (SUR1/Kir6.2), cardiac and skeletal muscles (SUR2A/Kir6.2), smooth muscles (SUR2B/Kir6.2), and vascular smooth muscles (SUR2B/Kir6.1) [ 22 ]. Of these, only Kir6.1/SUR2B is detected in the corpus luteum of the ovary and myometrium of the rat, while the placenta expresses Kir6.1 with SUR1 and SUR2B [ 23 ].…”
Section: Expression and Roles Of Potassium Channels In The Ovarymentioning
confidence: 99%